Comparing The Who 1997 / Who Searo 2011 And Who 2009 Dengue Classification In Diagnosing Dengue Infection In Out-Patient Settings In Tangerang District, Banten Province, Indonesia - Cucunawangsih Cucunawangsih (Medicinus, 2018)
The World Health Organization (WHO) 1997 / WHO (Regional Office of South-East Asia) SEARO 2011 and WHO 2009 dengue guideline emphasized different aspects. Indonesia as a limited resources hyperendemic area will a large number of patients hopitalized using the WHO 2009. This study compared the adult non severe dengue cases in out-patient settings using both classification. This retrospective cohort study on 85 patients found 48 dengue cases confirmed by reverse transcriptase polymerase chain reaction (RT-PCR) on the period of August 2011 – January 2012, in 5 out-patient settings health facilities. The sensitivity and spesificity of WHO 1997 / WHO SEARO 2011 were 48.93% and 23.68%, while the WHO 2009 were 78.72% and 68.42%. Out of 8 secondary infection patients, 25% in WHO 1997 / WHO SEARO 2011 and 0% in WHO 2009 were classified as the more severe form. The WHO 2009 shown higher sensitivity and specificity, but the WHO 1997 / WHO SEARO 2011 could diagnose more patient that would have suffered severe forms of dengue and also more secondary infection who have the probability of severe forms compared to WHO 2009.Keywords: dengue, out-patient setting, world health organization